DESAIN SISTEM KENDALI SUHU RUANG PEMANAS DENGAN METODE ULTIMATE CYCLE - Muhammad Amiruddin; Imadudin Harjanto; Bambang Hadi Kunaryo (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2024)
A room heating device equipped with a temperature control system that will be used to regulate the room temperature so that it is stable at a certain value. Before designing the hardware and setting the control methods that will be used, to simplify the design, a system response simulation is first carried out. In order to simulate the response of the temperature control system in the heating room, a mathematical model of the heating room and the temperature control system used is needed. Therefore, an approach using the FOPDT method is used to determine the mathematical model of the heating space. After obtaining a suitable mathematical model for the heating room in this research case, it is continued by providing a control gain (P-I-D) so that the performance of the heating room control system meets the requirements. To get the gain value (P-I-D), tuning is carried out using the ultimate cycle method. Providing Kp=0.06 to this temperature control system provides a steady state error performance of 5°C, rise time of 247 seconds and overshoot of 10°C. The addition of 1/Ti = 0.00133 and the change in Kp = 0.027 resulting from ultimate cycle tuning, have the effect of eliminating the steady state error but increasing the rise time to 530 seconds. The addition of Td = 112.5 and changes in 1/Ti = 0.0022 and Kp = 0.036 resulting from ultimate cycle tuning, have the effect of reducing the rise time to 380 seconds, but increasing the overshoot to 18°C